Morning glory [videorecording (DVD)] - Sherman, Lowell, 1888-1934; Hepburn, Katharine, 1907-2003; Fairbanks, Douglas, Jr., 1909-2000; Menjou, Adolphe, 1890-1963; Akins, Zoë, 1886-1958 (Warner Home Video, 2007)
Eva Lovelace is a would-be actress trying to crash the New York stage. She is a wildly optimistic chatterbox full of theatrical mannerisms. Her looks, more than her talent, attract the interest of a paternal actor, a philandering producer, and an earnest playwright. Is she destined for stardom or will she fade after her brief blooming.